Economization of Self: Constructing a Female Neoliberal Subject in Eílís Ní Dhuibhne’s Fox, Swallow, Scarecrow - Radmilo Derado, Sanja (Wydawnictwo Uniwersytetu Rzeszowskiego, 2024)
The paper focuses on the interdisciplinary textual analysis of Eílís Ní Dhuibhne’s Fox, Swallow, Scarecrow which addresses the complex human condition under the absolute reign of capitalism in the context of the Irish transition toward a neoliberal state. By relying on new economic criticism, the paper argues that this novel represents some of the silenced and, at the same time, most destructive aspects of the Irish iteration of neoliberal capitalism and its predominantly fictional character in the 21st century. By zooming in on the protagonists’ constant search for self-actualization amid the Irish economic and real-estate boom, the narrative reveals the confusion and desire inherent in the neoliberal state of mind which thrives on constant striving for materialistic self-fulfilment. Although the neoliberal paradigm introduced into the Irish public discourse the belief that women are finally in a position to realize themselves as active subjects and to enjoy benefits they had been denied in the past, this process is presented here as incomplete. Namely, the paper shows that at the height of Irish economic prosperity, within the short-lived and superficial social idyll, the characters live in a new form of capitalist colonialism in which they still encounter strong, albeit radically shaken social taboos such as class differences, poverty, extramarital affairs and women’s financial dependency in a marriage. The paper argues that the female neoliberal subject ultimately fails to adhere to the neoliberal paradigm on her journey toward self-assertion. She creates her own counter-space through her attempts to balance her intimate desires with the expectations placed on her as a wife and a mother. Threatened by unforgiving societal pressures, constructed counter-space critiques the neoliberal expectations of self-empowerment, but also challenges the patriarchal structures and traditional roles still imposed on women in modern Ireland.
Keywords: neoliberal subject; contemporary Irish fiction; textual representation; neoliberal state; reign of capitalism